(RE)THINKING SUFFERING AND MOURNING THROUGH COVID-19 PHOTOGRAPHS IN INDIA. (2nd January 2023) - Das, Purbita; Chatterjee, Antara
Abstract : This article offers a close textual and visual analysis of some of the most iconic photographs of the COVID pandemic's second wave in India, to examine how they evoke violence both within and outside the photographic frame, and become sites of critical reflection. The pandemic's second wave witnessed a proliferation of images in social media and online news portals representing mass deaths, corpses floating in rivers, and mass funerals executed in makeshift crematoria. Pointing out how the widely circulated photographs deployed an excess of violence to represent death as a dreaded event external to life, this article contends that the violence in these images not only evoked shock and horror but also interrupted mourning both in the private and the collective realm, furthered through violence in the images and the interruption of familiar mourning rituals for those dead. Deriving from Ariella Azoulay's idea of the 'civil gaze' to 'watch' photographs, the article explores how these photographs configure a space of critical reflection and responsibility towards those photographed, which uncovers the crucial biopolitical interfaces between disease, death, the state, and the precarity of citizens. It simultaneously deliberates on the role of the visual and the photographic gaze in foregrounding these intersections.